International experience of fight is against legalization of money obtained by a criminal way - Білько, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article attention applies on the features of the legal adjusting and process of realization of the financial monitoring by the foreign states. More detailed plenary powers and experience of the specialized organs are consideredin this sphere. The special scientific literature, and also legislation of Ukraine and other states, is in-process analysed in relation to this problem.